„Pure visibility” in Konrad Fiedler’s formal aesthetics - Kaźmierczak, Magda (Hybris, 2017)
Nowadays still not well known, Konrad Fiedler was an extremely original philosopher of art and an inspiring follower of Kant. He created a theory of art’s autonomy and his pioneering thought contributed not only to the formalist theory of art but also and foremost to creating an epistemology that later became a foundation of theories of art stressing the uniqueness of seeing and raising the status of visual representations. The artistic way of seeing, according to him, undiscloses the principles of how the world emerges from nothingness of chaotic sensations – it is the way of seeing that presents „pure visibility”. According to Fiedler, this way of seeing is the basis of each true artistic creative act.